Financial Surety : Guidelines for the Implementation of Financial Surety for Mine Closure - Sassoon, Meredith (World Bank, Washington, DC, 2014)
It is now accepted practice that when a company relinquishes a mining title, whether for an exploration or mining site, it is responsible for carrying out the rehabilitation of that site prior to departure. To ensure this is the case, most jurisdictions now require some form of closure plan or rehabilitation program to be submitted to the regulatory authority prior to the start of any work on the site. It is an increasingly common requirement for the closure plan to contain details of the estimated cost of rehabilitation and for a financial surety to be established at the same time. This report aims to provide governments with the information they need to make their own informed decisions. It is based on a review of existing financial surety systems in a number of countries. Questionnaires were sent out to a total of fourteen regulatory authorities; of these, nine provided sufficient detail about their existing financial surety systems to be included as full case studies. These are presented in the section case studies along with a summary of the latest European Union (EU) waste directives. Except where otherwise stated, the financial surety applies to all stages of a mining project, regardless of size. The purpose of the financial surety is to ensure that there will be sufficient funds to pay for site rehabilitation and post closure monitoring and maintenance at any stage in the life of the project, including early or temporary closure. The main aim of site rehabilitation is to reduce the risk of pollution, restore the land and landscape for an appropriate use, improve the aesthetics of the area, and prevent any subsequent degradation. The extent and cost of final site rehabilitation can be reduced if the site is rehabilitated even as it is being mined, so that the rate of restoration is similar to the rate of exploration or exploitation. This ideal is not often achieved, however; the majority of rehabilitation usually takes place once work on the lease has ceased.